Evaluation of the Effectiveness of Bitumen Emulsion for Stabilising Subgrade Sand - Arshad, Ahmad Kamil; Nathen, Jacqueline Michella; Mohamad Rais, Nuryantizpura; Shaffie, Ekarizan; Ismail, Fauzilah; Kamaluddin, Noor Azreena; Abdul Malek, Ahmad Zakilfikri (International Journal of Integrated Engineering, 2024)
Sand is a type of soil that is prone to erosion and has low bearing capacity. Hence, stabilisation of sand subgrade layer is needed. The results of a study assessing the efficiency of bitumen emulsions (2%, 3%, and 4%) for stabilising sand are presented in this paper. In this study, two different types of sand were individually mixed with bitumen emulsion: clayey sand and river sand. Soil classification, compaction test, California Bearing Ratio (CBR) and Unconfined Compressive Strength (UCS)  were among the laboratory tests conducted. The unsoaked and soaked CBR was measured after 4 days of curing, and the UCS of sand were measured after 7, 14 and 28 days of curing. Based on the obtained California Bearing Ratio (CBR) and Unconfined Compressive Strength (UCS), the results indicated that the sand was suitable to be stabilised with bitumen emulsion. It is recommended that future research conduct long-term studies to evaluate the performance of bitumen emulsion-stabilised poorly sand subgrade under real -world conditions